RESEARCH OF PROCESS OF AN ALLOYING OF THE FUSED COATINGS RECEIVED FROM THE SUPERFICIAL ALLOYED WIRE BY BORON WITH IN ADDITIONALLY APPLIED ELECTROPLATED COATING OF CHROME AND COPPER - V. A. Stefanovich; S. V. Borisov; A. V. Stefanovich (Литьë и металлургия)
Researches on distribution of chrome and copper in the fused coating received from the superficial alloyed wire by boron with in additionally applied electroplated coating of chrome and copper were executed. The structure of the fused coating consists of dendrites on which borders the boride eutectic is located. It is established that the content of chrome in dendrites is 1,5– 1,6 times less than in the borid; distribution of copper on structure is uniformed. Coefficients of digestion of chrome and copper at an argon-arc welding from a wire electrode with electroplated coating are established. The assimilation coefficient for chrome is equal to 0,9–1,0; for copper – 0,6–0,75.